Analisis Kesehatan dan Keselamatan Kerja di Laboratorium Biologi SMAN X Jakarta - Evi Muliyah; Zahra Azzahwa Avriliaputri; Arsya Niam Ul Husna; Ghalda Salsabila; Alicia Zahra Putri Marhali (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Occupational Health and Safety (OHS) is a crucial aspect in the management of school laboratories, particularly in supporting a safe and conducive learning environment. The implementation of OHS in laboratories is essential to prevent work-related accidents that may endanger students, teachers, and laboratory staff. This study aims to analyze the extent to which OHS principles are applied in the Biology Laboratory of SMAN X Jakarta. The research method used was observation and interview. Observations were conducted using a checklist adapted from the Laboratory Safety Self-Assessment Checklist, while interviews were carried out with the laboratory technician and two biology teachers as key informants. The data obtained were analyzed descriptively to provide a comprehensive overview of laboratory conditions and the implementation of safety measures. The results showed that the application of OHS in the Biology Laboratory of SMAN X Jakarta is categorized as very good. This is evidenced by adherence to safety procedures, the availability of personal protective equipment, and the rare occurrence of workplace accidents. Therefore, the laboratory is considered safe for conducting biology learning activities and can serve as a model for effective OHS implementation in school environments.